The Analysis of Y and Z Generation’s Soft Skill of Work Readiness in Using Social Media - Atika Atika; I Made Sudana; Sita Nurmasitah; Bayu Ariwibowo (International Journal of Active Learning, 2023)
The focus of this research is on the analysis of work readiness soft skills of Y and Z generation in using social media, namely Y and Z generation. Y and Z generation cannot be separated from social media, either in their daily life or their studies. Higher education institutions must determine the appropriate plans and strategies in developing human resources related to generations, especially in students’ readiness to meet the competencies needed by the industry, including the use of social media. The competencies expected by the industry are competence of attitudes which are classified as soft skills. This background becomes the foundation of research on the analysis of work readiness soft skills in Y and Z generation in higher education. The study was conducted on 250 students consisting of Y and Z generation who were differentiated based on the year of birth. The results showed that the acquisition rate was 66.48% (Y generation) and 67,350% (Z generation) which categoried as good. This means that they can use the social media to prepare themselves for the world of work after completing their studies at Higher Education. The analysis results can be used as an alternative for educators to determine teaching strategies.